Primo Bilancio di Genere dell'Ateneo Fridericiano First Gender Budgeting of - Maria Rosaria Masullo (Genere, scienza e società, 2016)
A Gender Budget is a strategic tool that provides an assessment of the political-economic and financial decisions of public administration from a gender-sensitive perspective. Its main goal is to support a more efficient, transparent, and equitable, management of resources. The first Gender Budget of the Università degli Studi di Napoli "Federico II" (UNINA) was realized within the framework of the European-Union funded GENOVATE research project: Transforming Organizational Culture for Gender Equality in Research and Innovation. It consists in a thorough context analysis of the University enrolment and career policy outcomes, encompassing students, academic, technical and administrative staff, which results in a detailed map of the still relevant gender gap dimension in the institution. Raw data and their focused analysis show how cultural and structural barriers contribute to women dropping out of university at the very beginning of scientific careers (i.e. the so-called 'leaky pipeline' phenomenon). Due to horizontal and vertical segregation mechanisms, some disciplinary fields and academic positions still remain dominated by one gender. It is the authors' hope that Gender Budgeting may become a well-established practice at UNINA, and may support transformative actions and inspire gender-mainstreaming institutional policies. GENOVATE is a project funded by the European Commission within the Seventh Framework Programme (FP7), under the Science in Society grant programme (SiS 2012 2.1.1-1). This volume was co-funded by the European Union.